Shakespeare's Tragic Language - Hammond, Paul, (Late Antiquity and Medieval Studies E-Books Online, Collection 2025., 2025)
In Shakespearean tragedy, language is used to bring about the downfall of characters, but there is also a tragedy which affects language itself through the decomposition of the fundamental concepts and mythologies which give identity to both societies and individuals. This book shows how in Shakespeare's English history plays, Roman plays, tragicomedies, and romances, characters use language to manipulate and destroy others, but also imprison themselves in false reasoning. The misuse of language creates tragedies for individuals but also for society at large, as its conceptual building blocks lose their capacity to function. For Shakespeare, tragedy happens both to individuals and to cultures, and happens both in language and to language.